Anaphylaxis should be recognized early and managed appropriately - Tanu, Megawati; Suryana, Ketut (International Journal of Advances in Medicine, 2023)
Anaphylaxis is a severe, systemic hypersensitivity reaction characterized by rapid in onset with potentially life-threatening. The prevalence of anaphylaxis has been estimated at 1.6% to 5.1% and increasing nowadays. Drug-Induce-Anaphylaxis is one the most cause of fatal anaphylaxis. A 26-year-old male with anaphylaxis shock due to drug-induced with total IgE as a diagnostic support test. Anaphylaxis is a multisystem allergic emergency. Early recognition and prompt administration of epinephrine remain the cornerstone of management due to its rapid progression.